Epitaxial Crystallization of Insulin on an Ordered 2D Polymer Template. Issue 15 (13th February 2019) - de Poel, Wester; Elemans, Johannes A. A. W.; van Enckevort, Willem J. P.; Rowan, Alan E.; Vlieg, Elias
Abstract: Two‐dimensional polymers (2DP) are a new class of materials that consist of a monolayer of ordered molecular building blocks, which have been covalently linked. One of these monomers was self‐assembled on a flat muscovite mica scaffold and subsequently the organic layer was polymerized. The resulting flat and stable 2DP layer was used as a template for protein crystallization. Crystals of insulin were epitaxially grown on the template, whereas insulin crystals grown on clean muscovite mica had a random orientation. The template was selective, considering that no epitaxially ordered crystals formed of hen egg white lysozyme, bovine serum albumin, or talin. Abstract : A 2D polymer network on a muscovite mica template was used for epitaxial insulin crystallization. The bare mica scaffold, the 2D polymer on top, and finally the insulin layer are shown from left to right (see figure).